Pengembangan Game Edukasi untuk Meningkatkan Hasil Belajar IPAS Siswa Sekolah Dasar berbasis Case Method dan Team Based Project - Prayudi, Andi; Sasmita, Lita; Supriyaddin, Supriyaddin; Burhanuddin, Burhanuddin; Mahdin, Mahdin (Jurnal Kridatama Sains dan Teknologi, 2025)
This study aims to develop an educational game to improve the learning outcomes in Social Sciences and Natural Sciences (IPAS) for students at SDN 14 Dompu, based on the case method and team-based project approaches, which is valid, practical, and effective. This research employs the Research and Development (R&D) method using the 4-D. The results show that the IPAS educational game has a feasibility percentage of 80%, which falls into the feasible category, and a practicality level of 74%, indicating that the game is practical to use. Furthermore, the evaluation of effectiveness shows that students’ pre-test score was 57%, suggesting moderate effectiveness at the initial stage, while the post-test score increased to 73%, indicating that the game is effective to use, resulting in a 16% improvement in learning outcomes. Therefore, it can be concluded that the developed IPAS educational game is feasible, practical, and effective for improving students' learning outcomes in IPAS.